Passage of time - Alpern, Amerinda, author; Voss, Gary Wayne, advisor; Alexander, Ruth M., committee member; Kokoska, Mary-Ann, committee member; Lundberg, Thomas R., committee member (Colorado State University. Libraries, 2006)
This collection of work is an expression of my changing body and psyche as a middle-aged woman. For me this is a transformative time of living on the edge between the two halves of my life, young and old. I've chosen to work with the depictions of women's breasts because they are the central icons of femininity; they represent the generative, nurturing aspects of women, as well as their sexual nature. Although identity changes throughout one's life, these times of passage offer opportunities for intense reflection while the body and psyche reconfigure themselves. Changes in the soft tissues of the body occur with time. The breast is one of the more noticeable areas of the body that exhibits these changes. At mid-life, while observing these changes, a woman has the opportunity to consciously let go of socially imposed standards of how she should behave and look, and redefine herself on her own terms. During the process of making molds of many women's breasts, I discovered and wanted to demonstrate how completely unique they are, ranging from the breasts of early adulthood, small and firm, to the weight and distortion that aging brings. Of the range of women who participated in the casting process, one woman was still lactating, other women had nursed their children many years ago, and there were women who have not had children. These castings represent transition away from youth into the unknown, into mysteries yet to unfold. I have chosen to express these ideas through the use of clay, plaster, and bronze. Clay is a fragile substance before firing, soft and malleable like breast tissue. Once fired, the clay castings become more fragile, like dried delicate tissue. Plaster can be used as an intermediary material in the mold-making process or as an end product in sculpture. Fragile plaster castings make way for the strength of bronze. Bronze, like the strength of tempered women is an enduring medium withstanding the passage of time. The wall-mounted breasts represent the underlying unity of women's experiences through time. The small bronze works embody my emotional passages of womanhood, the reconfiguring of self, the release of youth, and the welcoming of wisdom.
Keywords: Modeling (Clay, plaster, etc.); Breast in art